RECONFIGURING SUFISM EDUCATION IN THE 21st CENTURY: Exploring Spiritual Crossroads among Millennials in Padang City - Eliana Siregar; Susilawati Susilawati (MIQOT: Jurnal Ilmu-ilmu Keislaman, 2026)
Sufism education has long been a cornerstone of Islamic spirituality, yet in the 21st century it faces new challenges from globalization, digitalization, and shifting youth religiosity. This study explores how Sufism education is transformed and rearticulated among millennials in Padang City, Indonesia, highlighting the interaction between traditional teachings and contemporary learning environments. Using qualitative methods, data were collected through in-depth interviews, participant observation, and analysis of digital Sufi discourse. Findings reveal a hybrid model: traditional institutions such as pesantren, majlis dzikr, and university study circles remain central for transmitting texts, spiritual discipline, and mentorship, while digital platforms—social media, online lectures, and virtual study groups—expand access and engagement. Millennials reinterpret Sufi practices in psychological and self-developmental terms, framing dzikr as a tool for mindfulness, emotional regulation, and spiritual well-being. These results suggest that digital and traditional modes complement one another, offering flexible pathways for spiritual formation and shaping the evolving spiritual identities of urban Muslim youth.